PERILAKU BERPACARAN PADA REMAJA DI DESA BATUBELAH KECAMATAN KAMPAR KABUPATEN KAMPAR - Wiwit Indrayani; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Society today is in a social system which tend to start removing the values of the past. This situation not only in society in big cities but also move to the countryside caused by the effect of technological advances and the waning of social control, so major changes experienced by teenagers because they tend to follow the trend without much thought about the good or bad risks, including in dating behavior. Formulation of the problem is how the behavior of teenage dating in Batu Belah Village and how to control teenage dating. The purpose of this study is to determine the extent of teen dating behavior and how the role of parents and the community in monitoring the behavior of teenage dating in Batu Belah village. The theory used is the theory of structural functionalism, the theory of social change and the theory of direction of change. This research was conducted in Batu Belah village District Kampar, Kampar Regency. This research is a qualitative descriptive subject in the study is that adolescents dating totaling 5 people and older people (public figures) 5 respondents. The object of this study is the behavior of teenagers in dating. to gather data, researchers used purposive sampling method. In analyzing the research data used quantitative analysis to explain all the processes found in the field.Keyword: Dating Behavior, Community Control, social change